Stolen magic - Levine, Gail Carson (Harper, 2016)
Elodie, dragon detective Meenore, and the ogre Count Jonty Um travel to Elodie's home on the island of Lahnt. However, when they arrive, they discover a statue that keeps the local volcano from erupting has been stolen. Elodie must use her wits to find the statue before the volcano erupts and destroys her island home.